Acceptability of Cereal-Cricket Composite Porridge as Influenced by Socio-Economic Factors and Breast-Feeding Status of Mothers and Care-Givers in Siaya County, Kenya - Aboge, Danstone Ochieng (JOOUST, 2024)
The trajectory for widespread integration of edible insects into the human diet is still confronted by low acceptability especially among communities that traditionally or habitually do not consume insects. While the concern today is how best to present edible insects into food matrices that improve their acceptability, this development should be aligned with consumer intrigues into the choices of insect-based foods. This study determined the influence of socio-economic factors (age, education, marital status, occupation, and income levels), and breastfeeding status of mothers and care givers on acceptability of cricket-based porridges. Four composite porridge flours were developed by blending cricket flour with maize, wheat, and soy flour at four different levels. The reference formula (CP) had 0% cricket inclusion and was a composite of maize, wheat, and defatted soy flour in the ratio of 2:1:1 resembling Famila Baby weaning porridge flour, a common infant formula in Kenya. The other treatment flours were formulated by replacing an equivalent amount of soy flour with cricket flour at 25%, 50% and 75% to allow enrichment of Famila formula with cricket flour, and were coded as CPB1, CPB2 and CPB3, respectively. Porridge prepared from the flours were evaluated for acceptability among forty mothers and care-givers selected in Siaya County, Kenya. Non-cricket porridge was the most accepted across the respondents’ socioeconomic dynamics. Acceptability of cricket-based porridges improved with age and level of education but reduced significantly for both married (p<0.000) and unmarried women (p<0.000). Women engaged in formal employment rated cricket-based porridges significantly higher (p<0.003) than other occupations. Income level generated mixed influences with non-cricket porridge still rated significantly higher (p<0.000) than cricket-based porridges across different income groups. Breastfeeding had insignificant influence on acceptability of the porridges (p=0.06). From this study, age, education, occupation and income showed varied influences on the acceptability of cereal-cricket porridges and should therefore be considered among key factors that shape consumer acceptability. Consequently, promotion strategies should consider the latter socio-economic factors in devising interventions to improve acceptability of edible insects and their products.
Keywords: Edible Insects; Crickets; Porridge; Socio-economic status; Consumer evaluation; Acceptability